Mechanisms involved in VPAC receptors activation and regulation: lessons from pharmacological and mutagenesis studies. - Langer, Ingrid (Frontiers in Endocrinology, 2012)
VIP plays diverse and important role in human physiology and physiopathology and their receptors constitute potential targets for the treatment of several diseases such as neurodegenerative disorder, asthma, diabetes and inflammatory diseases. This article reviews the current knowledge regarding the two VIP receptors, VPAC1 and VPAC2, with respect to mechanisms involved in receptor activation, G protein coupling, signaling, regulation and oligomerization.